Multiannual assessment of the desert dust impact on air quality in Italy combining PM10 data with physics-based and geostatistical models. (May 2022) - Barnaba, Francesca; Alvan Romero, Nancy; Bolignano, Andrea; Basart, Sara; Renzi, Matteo; Stafoggia, Massimo
Graphical abstract: Highlights: We quantify the impact of desert dust on particulate matter air quality over Italy. We derive a multiannual dataset of desert dust-PM10 values resolved by site and day. In Italy desert dust contributes to exceed PM10 limit values fixed by EU and WHO. Random forest modelling is used to obtain a spatially continuous dust-PM10 field. Geostatistical model outcomes will serve as a basis to study dust impact on health. Abstract: Desert dust storms pose real threats to air quality and health of millions of people in source regions, with associated impacts extending to downwind areas. Europe (EU) is frequently affected by atmospheric transport of desert dust from the Northern Africa and Middle East drylands. This investigation aims at quantifying the role of desert dust transport events on air quality (AQ) over Italy, which is among the EU countries most impacted by this phenomenon. We focus on the particulate matter (PM) metrics regulated by the EU AQ Directive. In particular, we use multiannual (2006–2012) PM10 records collected in hundreds monitoring sites within the national AQ network to quantify daily and annual contributions of dust during transport episodes. The methodology followed was built on specific European Commission guidelines released to evaluate the natural contributions to the measured PM-levels, and was partially modified, tested and adapted to the Italian case in a previous study. Overall, we show that impact of dust on the yearly average PM10 has a clear latitudinal gradient (from less than 1 to greater than 10 µg/m 3 going from north to south Italy), this feature being mainly driven by an increased number of dust episodes per year with decreasing latitude. Conversely, the daily-average dust-PM10 (≅12 µg/m 3 ) is more homogenous over the country and shown to be mainly influenced by the site type, with enhanced values in more urbanized locations. This study also combines the PM10 measurements-approach with geostatistical modelling. In particular, exploiting the dust-PM10 dataset obtained at site- and daily-resolution over Italy, a geostatistical, random-forest model was set up to derive a daily, spatially-continuous field of desert-dust PM10 at high (1-km) resolution. This finely resolved information represent the basis for a follow up investigation of both acute and chronic health effects of desert dust over Italy, stemming from daily and annual exposures, respectively.